Kiribati : 2017 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Kiribati's economic fundamentals have strengthened in recent years. Strong fishing revenue improved the fiscal position, strengthened the current account, and boosted business confidence. After registering a double-digit rate in 2015, real GDP growth declined to 1.1 percent in 2016, but is projected to pick up to about 3 percent in 2017 driven by construction and wholesale and retail trade. The authorities have made commendable progress in structural reforms. They have implemented important reforms to improve the governance and management of the Revenue Equalization Reserve Fund and replenished the fund from the cash reserves. Despite a favorable economic outlook, risks to near-term growth are substantial and skewed to the downside.